An analysis of the risk and limitations of placing reliance on lifestyle audits in the fight against corruption and tax evasion in South Africa - Hill, Tanya (University of Pretoria, 2023)
Mini Dissertation (MCom (Taxation))--University of Pretoria, 2022.